2014
DOI: 10.1021/ma500664u
|View full text |Cite
|
Sign up to set email alerts
|

From Polymer Sequence Control to Protein Recognition: Synthesis, Self-Assembly and Lectin Binding

Abstract: A novel, highly efficient methodology to synthesize gradient glycopolymers has been successfully developed involving concurrent enzymatic monomer transformation and reversible addition−fragmentation chain transfer (RAFT) polymerization. By synchronizing enzymatic monomer transformation with polymerization, a continuous supply of the second monomer (glycomonomer) is achieved during the polymerization, resulting in a gradient sugar distribution in the final polymer. Detailed studies of the process using GPC and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
39
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 50 publications
0
39
0
Order By: Relevance
“…27,28 A library of galactosylated polymers with different statistical, gradient, and block microstructures were proven to have higher aptitude in clustering Ricinus communis (castor bean) agglutin RCA 120 than other glycopolymers. 29 Glycopeptide dendrimers based on galactose also showed high affinity to LecB and LecA lectins, and efficiently induced the biofilm dispersal of Pseudomonas aeruginosa. 30 It is thus a promising concept to employ glycopolymers in the design of antimicrobial compounds for modulating toxicity and simultaneously targeting bacterial cells.…”
mentioning
confidence: 99%
“…27,28 A library of galactosylated polymers with different statistical, gradient, and block microstructures were proven to have higher aptitude in clustering Ricinus communis (castor bean) agglutin RCA 120 than other glycopolymers. 29 Glycopeptide dendrimers based on galactose also showed high affinity to LecB and LecA lectins, and efficiently induced the biofilm dispersal of Pseudomonas aeruginosa. 30 It is thus a promising concept to employ glycopolymers in the design of antimicrobial compounds for modulating toxicity and simultaneously targeting bacterial cells.…”
mentioning
confidence: 99%
“…[42][43][44][45][46][47][48][49][50][51][52][53][54][55] Recent studies have reported that polymer structures (i.e., sequences and topology structures) remarkably affect the properties or functions of polymers. 53,[56][57][58][59][60] Thus, the future combination of these modern CRP techniques with the method used herein might offer new polymeric probes for the more rapid, more precise detection of FA in biological systems.…”
Section: Possible Extensions and Challengesmentioning
confidence: 99%
“…An amphiphilic sugar‐containing gradient copolymer was further synthesized by employing protected galactose as alcohol substrate via this one‐pot method (Fig. ) . The influence of the macromolecular architecture, i.e.…”
Section: Applications Of One‐pot Current Enzyme‐crp Systemmentioning
confidence: 99%
“…One‐pot synthesis of gradient glycopolymer via concurrent enzymatic monomer transformation and RAFT polymerization and the effects of monomer sequence in the polymer on protein binding. Reproduced with permission . Copyright 2014, American Chemical Society.…”
Section: Applications Of One‐pot Current Enzyme‐crp Systemmentioning
confidence: 99%